2002
DOI: 10.1016/s0735-1097(02)02535-4
|View full text |Cite
|
Sign up to set email alerts
|

Circadian variation of blood pressure and endothelial function in patients with essential hypertension

Abstract: These findings suggest that endothelium-dependent vasodilation is blunted through a decrease in NO release in non-dippers compared with patients who have dipper hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
4
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 19 publications
6
103
4
3
Order By: Relevance
“…Various other studies investigating the effects of dipping and non-dipping patterns demonstrated that patients with non-dipping pattern have been associated with an increased risk of end-organ damage (Cuspidi et al 2004a) such as cerebrovascular and cardiovascular complications than other patients with dipping pattern (Staessen et al 1999;Kario et al 2001;Higashi et al 2002). Although underlying mechanisms are still unknown, sympathetic over activity, functional and structural vascular alterations, early autonomic neuropathy have all been seen in patients with non-dipping BP (Hommel et al 1989;Sherwood et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Various other studies investigating the effects of dipping and non-dipping patterns demonstrated that patients with non-dipping pattern have been associated with an increased risk of end-organ damage (Cuspidi et al 2004a) such as cerebrovascular and cardiovascular complications than other patients with dipping pattern (Staessen et al 1999;Kario et al 2001;Higashi et al 2002). Although underlying mechanisms are still unknown, sympathetic over activity, functional and structural vascular alterations, early autonomic neuropathy have all been seen in patients with non-dipping BP (Hommel et al 1989;Sherwood et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…44 Sodium Sensitivity-Nondipping has been associated with sodium sensitivity in hypertensive patients, 45 and both sodium restriction 45;46 and thiazide diuretics 47 have been shown to restore dipping in these salt sensitive patients. Potential mechanistic links between salt sensitivity and nondipping include impaired baroreflex function leading to sympathetic activation 48 and impaired endothelial function, which is both common in nondippers 49 and which has been shown to be associated with salt sensitivity in an animal model. 50 With the above in mind the high prevalence of nondipping in CKD should come as no surprise, in particular because CKD is well known to be associated with increased sympathetic activation.…”
Section: Physiology Of Dippingmentioning
confidence: 99%
“…6 In fact, many studies suggest that patients who do not show an appropriate nocturnal dip in BP can suffer from a variety of disorders associated with increased rates of cardiovascular morbidity and mortality. [7][8][9] Ohkubo et al 10 have shown that a blunted nocturnal decline in BP was a risk factor for cardiovascular mortality in the general population. In this regard, Cuspidi et al 7 have shown that the persistence of a non-dipper pattern is associated with an increased left ventricular mass index, a thicker interventricular septum and a larger diameter of both the left atrium and the aortic root, in a group of 375 previously untreated hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…8 These non-dipper hypertensive patients have a more severe impairment of endothelial function as manifested by a reduced ability of endothelium-dependent vasodilation, mediated by a decrease in nitric oxide release. 9 In fact, reverse dippers show wider pulse pressure at night than any other groups, suggesting the potential role of arterial stiffness as an underlying mechanism of impaired cardiovascular risk. 11 All these changes determine a worse long-term prognosis of those hypertensives with absence of nocturnal dip in BP.…”
Section: Introductionmentioning
confidence: 99%